Facebook Training to Increase Sales of Clothing Merchants in Cimahi-Mall, Cimahi - Rendra Trisyanto Surya; Riauli Susilawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The role of the Politeknik campus as an applied (vocational) higher institution, which carries out the Tri Dharma of Higher Education, namely Research, Education and Community Service causes the socio-economic problems of the surrounding community to become the moral responsibility of this campus. Cimahi-Mall, which is only located less than 10 Km from Politeknik Negeri Bandung (POLBAN) Campus, then provides its own challenges to be able to play an active role in solving the problem. The development of information technology, especially social media, has been so rapid and has spread evenly to various circles of society. However, on the other hand, there are still many people who cannot use it optimally for various reasons and reasons. In fact, social media applications such as Facebook, have been equipped with a variety of features that are also quite complete for conducting online business activities. One of them is what is called Facebook Ads, which now allows users to market their products/services to the general public of more than 100 million Facebook application users. In the city of Cimahi alone there are more than 101,000 users. On the other hand, tenants (sellers) at Cimahi-Mall actually fit the online business criteria because they sell clothing products, and can take advantage of this demographic data if they actively use Facebook to introduce their products. From the results of the Facebook Training held by the Community Service Program, it was evident that there was an increase in participants' understanding of Facebook Ads and the Digital Marketing Concept from 52% to 67%